Skewed representation of functionally distinct populations of virus-specific CD4 T cells in HIV-1–infected subjects with progressive disease: changes after antiretroviral therapy - Harari, Alexandre; Petitpierre, Stéphanie; Vallelian, Florence; Pantaleo, Giuseppe (Blood, 2004)
HIV-1- and cytomegalovirus (CMV)-specific CD4 T-cell-mediated antiviral immunity was evaluated by assessing the frequency of interleukin 2 (IL-2)- and interferon γ (IFN-γ)-secreting cells following antigen-specific stimulation in blood and lymph node. HIV-1-infected subjects with progressive disease at early stage of infection with no previous history of antiretroviral therapy (ART), subjects with nonprogressive disease, and HIV-negative subjects were studied. On the basis of the ability to secrete IL-2 and IFN-γ, 3 functionally distinct populations of CD4 T cells were identified: (1) IL-2-secreting cells; (2) IL-2/IFN-γ-secreting cells; and (3) IFN-γ-secreting cells. CMV-specific CD4 T cells were almost equally distributed within the 3 functionally distinct cell populations in the 3 study groups as well as HIV-1-specific CD4 T cells in subjects with nonprogressive disease. However, a skewing toward IFN-γ-secreting cells (70% of HIV-1-specific CD4 T cells) was observed in subjects with progressive disease, and IL-2- and IL-2/IFN-γ-secreting cells were almost absent. The frequencies of IL-2- and of IL-2/IFN-γ-secreting HIV-1-specific CD4 T cells were negatively correlated with the levels of viremia. Interestingly, prolonged ART was able to correct the skewed representation of different populations of HIV-1-specific CD4 T cells but was associated with only a partial recovery of IL-2-secreting cells. These results indicate that the composition of the pool of functionally distinct virus-specific CD4 T cells is important for virus control. (Blood. 2004;103:966-972)